National Role Conceptions And Regional Rivalry: The Dynamics Of Iran-Azerbaijan Role Conflict In The South Caucasus - Tadevosyan, Suren (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
This study utilizes role theory to analyze how contrasting National Role Conceptions (NRCs) shape the foreign policies of Iran and Azerbaijan in the South Caucasus. Iran's NRC as a "Defender of Islam" arises from its identity as a Shia Islamic republic committed to safeguarding Shia communities and promoting Islamic governance. In contrast, Azerbaijan's NRC as a "Secular Modernizer" is rooted in its post-Soviet emphasis on secular governance and alignment with Western institutions. The research explores how these divergent NRCs lead to role contestation, influencing each state's strategies. By examining Iran's support for religious institutions, educational initiatives, media outreach, and cultural diplomacy, the study illustrates Iran's efforts to expand its ideological influence and challenge Azerbaijan's secular orientation. Azerbaijan counters with regulatory measures, state-controlled religious education, media management, and strategic alliances to reinforce its secular identity. This interplay highlights the crucial role of identity in shaping foreign policy beyond material considerations. The findings demonstrate the importance of NRCs in understanding state behavior in identity-driven conflicts, impacting regional dynamics and stability.
Keywords: Role theory